The Management of Anesthesia-Related Drug Shortages: A Systems-Level Crisis Response - Sadly, Norah Mohammed; Wafa Saeed Aldosari; Eman Alhumidi AlEnazi; Maged Ahmed Ali AbuAlghith; Ali Saleh M Saied; Aboud Jound Ageel Abuieisha; Bandar Mohsen Ahmed Alamri; Saud Daifallah Darraj; Mohammad Hossain Aldoseri; Ali Khudhyr Alyami; Yousef Jamman Alharbi; Abdulrahman Abdulla Ali Al-Dosary; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Anesthesia-related drug shortages pose a significant threat to global healthcare, impacting patient safety and surgical outcomes. Shortages of essential drugs, such as propofol and opioids, force clinicians to use unfamiliar alternatives and adjust protocols. These shortages result from complex supply chain issues, including manufacturing quality problems and material scarcities. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes evidence from 2010 to 2024 on interdisciplinary, systems-level strategies for mitigating the impact of anesthesia drug shortages. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive search of PubMed, Scopus, CINAHL, and regulatory agency databases was conducted. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evidence indicates that effective management requires a tiered, team-based approach. Pharmacy must lead supply chain surveillance and develop evidence-based substitution protocols. Anesthesia must adapt clinical techniques, employing multi-modal analgesia and regional anesthesia to reduce reliance on scarce agents. Nursing is critical for patient monitoring, education, and ensuring continuity of adapted care plans. Successful institutional responses are characterized by centralized drug shortage committees, real-time communication, and simulation training for crisis scenarios. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Anesthesia drug shortages are not transient disruptions but endemic features of modern healthcare. Mitigating their impact requires moving from ad-hoc, reactive responses to embedded, interdisciplinary preparedness plans that prioritize patient safety through shared stewardship, protocolized adaptation, and transparent communication across the perioperative team.